Analysis The Success of Knowledge Management in Agile Team Study Case: Ecommerce in Indonesia - Yanpratama, Agas; Raharjo, Teguh (AI Society & STMIK Indonesia, 2023)
Information in organizations needs to be managed to gain a competitive advantage in competitions. E-commerce, one of the most prominent industries in Indonesia, has dynamic market conditions that frequently change requirements and recent layoffs, which can harm the companies if not correctly managed. Knowledge and information usually stored in a knowledge management system (KMS) are essential to negate this, and Agile software development methodologies can manage frequent requirement changes. However, a study about KMS's success in Agile teams, primarily e-commerce, needs to be conducted to know if KMS can help companies sustain their business in Indonesia. This research analyses the KMS success in Indonesia's e-commerce companies that use Agile as their software development methodologies. This study used a quantitative approach with 31 respondents who worked or previously worked in an e-commerce company in Indonesia, using Agile as software development methodologies and experienced using KMS daily. Data was processed and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) and SmartPLS tools. The results of this study indicate that KMS net benefits in Agile teams in E-commerce in Indonesia are influenced by the user's intentions to use and user satisfaction when using the KMS.